Web-Based Student Thesis Information System of Electrical Engineering Department Trunojoyo University Madura - Muhammad Ilham Rasyidi; Diana Rahmawati; Riza Alfita; Miftachul Ulum (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2022)
The management of student academic data in thesis files in the Electrical Engineering Department, Trunojoyo University Madura (UTM) is still manual, resulting in a waste of time and energy in delivering information. In this study, the current system flow in UTM electrical engineering is described, then carried out by designing an effective system. The system design consists of a database design process. The system design consists of the database design process, web-based user interface design, and HTML creation (HyperText Markup Language). Designing a web-based thesis information system is the purpose of this study. It is displayed through a 50” inch monitor using a mini PC to present thesis information, progress in thesis work, details of the load supervisors, facilities that support students, and admins in making thesis administrative completeness. Later the system is designed to have a database that is useful for storing data and a web-based user interface to enter and retrieve the required data to be accessed anywhere, by several users en masse via an internet connection. The information presented is up to date.